Investigation of the positioning accuracy of the Cat’s Eye as a reference position in asphere-measuring interferometry - Scholz Gregor; Evers Daniel; Fortmeier Ines (Journal of the European Optical Society-Rapid Publications)
The increasing interest of the optics manufacturing industry in apshere and freeform optics leads to a high demand in accurate form measurement of such surfaces. The tilted-wave interferometer offers a fast and flexible solution to the needs. However, similar to other interferometric methods, ambiguities between specimen misalignment and certain form errors exist. To ensure the accuracy of the form measurement, the accuracy of the specimen positioning is crucial. This work presents a multi-step specimen positioning procedure that uses the Cat’s Eye reference position as a fixed reference position. Different alignment criteria are evaluated by simulation and implemented into an alignment algorithm for specimen alignment into the Cat’s Eye position. The procedure, investigated with multiple test specimens, shows a good short-term repeatability with a standard deviation below 30 nm. The use of this specimen alignment procedure will significantly reduce surface form measurement errors associated with axial misalignment and improve the overall measurement accuracy of the tilted-wave interferometer.